2018
DOI: 10.1016/j.worlddev.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of foreign remittances on poverty in Nepal: A panel study of household survey data, 1996–2011

Abstract: Using data from the longitudinal panel surveys of 1996, 2004, and 2011, this paper examines the dynamics of foreign remittances and their impact on poverty in Nepal. The intent is to explore how foreign remittances have evolved and impacted poverty and economic well-being of households. Focusing on a consistent set of households across the three survey rounds in a balanced panel format helps examine the effect of foreign remittances with appropriate controls. Results from methodologically consistent, random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 30 publications
(58 reference statements)
0
33
0
2
Order By: Relevance
“…Among the studies that attempted to establish the relationship between poverty and remittance, the results largely reflect a positive relationship (Adam and Page 2005;Acosta 2008;Gupta et al 2009; Fuente 2010; Anyanwu and Erhijakpan 2010; Adam and Cuecuacha 2013; Akobeng 2016; Nahar and Arshad 2017; Vacaflores 2018; Tsaurai 2018). However, there are other studies that found the relationship to be dependent on the country of study, methodology and time under investigation (Azam et al 2016;Wangle and Devkota 2018). Adam and Page (2005) in a study on 71 developing countries investigated the impact of remittance on poverty.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Among the studies that attempted to establish the relationship between poverty and remittance, the results largely reflect a positive relationship (Adam and Page 2005;Acosta 2008;Gupta et al 2009; Fuente 2010; Anyanwu and Erhijakpan 2010; Adam and Cuecuacha 2013; Akobeng 2016; Nahar and Arshad 2017; Vacaflores 2018; Tsaurai 2018). However, there are other studies that found the relationship to be dependent on the country of study, methodology and time under investigation (Azam et al 2016;Wangle and Devkota 2018). Adam and Page (2005) in a study on 71 developing countries investigated the impact of remittance on poverty.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Poverty alleviation programs have received great attention worldwide [8,10,25]. To target the poor, the Chinese government has invested greatly in community based programs [1,48].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing poverty has been the major task of the government to improve social development [1][2][3], boost economic growth [4][5][6] and benefit individual welfare [7][8][9][10]. According to the World Bank [11], the population of people living in poverty decreased from 35% in 1990 to 11% in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Due to data accessibility, our study period was limited to the period from 2005 to 2011 in Nepal. However, compared with the existing studies on Nepal poverty [4,19,22,23,[47][48][49][50][51][52][53][54][55][56][57][58][59], this study provided a contextual background on the overall trend of poverty change, the poverty concentration, the spatial change of UP (PI, PG and SPG), and the combination mode of UP-economic development along different dimensions and at district scales. This provided the opportunity to elucidate and consider potential drivers of development at a national scale.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, Nepal has instigated a range of poverty reduction and development programs [3], which have helped reduce poverty in the county, although there are still distinct problems, particularly in mountainous rural areas where the poverty gap remains large. Poverty research for Nepal has concentrated on the connection between poverty and income [47], the influence of migration and remittances on poverty [48,49], household livelihood options for the implication of rural pro-poverty [50], environmental reliance of household income and poverty reduction [51][52][53], public facilities or services for alleviating poverty in difficult terrains, such as rural road construction [54] and energy accessibility [55], as well as the nexus between poverty and political conflicts, including violence and wars [56][57][58].…”
Section: Introductionmentioning
confidence: 99%